Influence of Agreeableness and Openness to Experience Personality Traits on Biology Students’ Achievement in Bosso Local Government Area, Niger State, Nigeria - Nkok, Ekaette Anietie Enang; Obabori, Hezikiah Friday (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This research investigated the influence of agreeableness and openness to experience personality traits on academic achievement of Biology students in Bosso Local Government Area of Niger State. A survey research design was employed to investigate two of the Big Five personality traits of openness to experience, and Agreeableness on academic achievement of secondary schools Biology students, the population of the study comprised of 7550 SSII Biology students. A sample size of 365 students 184 males (40%) and 217 females (60%) were selected using Hat and Draw random sampling techniques. Two instruments were employed in the study; (a) The Multimodal Personality Inventory (MmPI) and (b) 2022/2023 third Term Biology Examinations Scores (FTBES). The coefficients of reliability of the instruments were such that Agreeableness had 0.73, and Openness to Experience had 0. 82. Two research questions were asked and two hypotheses formulated and tested at 0.05 level of significance using Product moment correlation coefficient. one of the hypotheses was rejected while one was upheld. The findings of the study reveal that; openness to experience had the highest Biology achievement score of 0.78 and p-value= 0.00, while agreeableness personality trait with Biology achievement score of 0.07 and p-valve=0.138, the findings of the study revealed that there is a strong relationship between openness to experience and Biology achievement of students and no significant relationship between academic achievement and agreeableness personality traits. two recommendations were made, among which is that. teachers should encourage students with openness to experience personality traits through the use of reward and positive reinforcements so as to sustain the explorative behavior which has positive influence in their academic achievement.